2017
DOI: 10.1016/j.ajpath.2016.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin Induces Inositol Trisphosphate–Mediated Spatially Extensive Responses in Lung Microvessels

Abstract: Activation of plasma membrane receptors initiates compartmentalized second messenger signaling. Whether this compartmentalization facilitates the preferential intercellular diffusion of specific second messengers is unclear. Toward this, the receptor-mediated agonist, thrombin, was instilled into microvessels in a restricted region of isolated blood-perfused mouse lungs. Subsequently, the thrombin-induced increase in endothelial F-actin was determined using confocal fluorescence microscopy. Increased F-actin w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
0
1
0
Order By: Relevance
“…Previous studies have demonstrated the thrombin-induced permeability increment within Transwell chamber in vivo and observed thrombin-induced organ permeability in vitro (Escue et al, 2017). Clinically, the causal role of thrombin in lung ischemia-reperfusion injury has been established (Farivar et al, 2006).…”
Section: S1pr2 Is Critical To Thrombin-induced Tissue Level Permeability Changesmentioning
confidence: 99%
“…Previous studies have demonstrated the thrombin-induced permeability increment within Transwell chamber in vivo and observed thrombin-induced organ permeability in vitro (Escue et al, 2017). Clinically, the causal role of thrombin in lung ischemia-reperfusion injury has been established (Farivar et al, 2006).…”
Section: S1pr2 Is Critical To Thrombin-induced Tissue Level Permeability Changesmentioning
confidence: 99%
“…The propagation of intercellular Ca 2+ waves in the vascular intima can be supported either by the diffusion of cytosolic second messengers [128,139], e.g., Ca 2+ and/or InsP 3 , through gap junctions or by the paracrine release of extracellular mediators [140,141], e.g., ATP. An alternative mechanism has been proposed for the hemodynamic response to prolonged (5 s) somatosensory stimulation in the whisker barrel cortex.…”
Section: Intercellular Ca 2+ Waves In Vascular Endothelial Cellsmentioning
confidence: 99%